Leadership Style and Communication in Conflict a Settlement at PLN Branch Gebang - Fachruddin Hariandi; Kiki Farida Ferine; Yohny Anwar (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
This study aims to see how the influence of communication and leadership on conflict resolution. Communication and leadership, which is an integral part of the organization, generally have a strong influence on the organization or even not, depending on how they communicate and use their leadership in managing the organization. The research method used is correlational research which aims to detect the extent to which variations in one factor are related to variations in other factors based on the correlation coefficient. Organizational communication structure is defined as a system of pathways through which messages flow or as a pattern of interaction between the people who make up the organization (Nica in Hener, 2010). Leaders influence others through their ability to motivate, inform, inspire, have technical competence, communicate effectively, and convey a vision (Pierce & Newstrom in Kaimenyi, 2014). Organizational conflict is a disagreement between individuals or groups within the organization, focusing on factors ranging from resource allocation and division of responsibilities to the employee organization as a whole (Hossain, 2017).